2011
DOI: 10.1007/s10549-011-1465-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in women with small (T1mic,T1a,T1b) node-negative operable breast cancer by immunohistochemically selected subtypes

Abstract: International audienceKnowledge is limited about prognostic significance of breast cancer subtypes among women with small invasive node-negative breast tumours. We explored patterns of recurrence in 1691 women with pT1mic/T1a/T1b, pN0 and M0 breast cancer according to four immunohistochemically defined tumour subtypes: (i) Luminal A (ER-positive, PgR-positive, HER2-negative and Ki-67 < 14%); (ii) Luminal B (ER-positive and/or PgR-positive, HER2-positive and/or Ki-67 ≥ 14%); (iii) HER2-positive, both endocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 20 publications
3
54
1
3
Order By: Relevance
“…Some studies observed that HER2 þ and/or Basal subtype tumors have a significantly higher risk of local failure than LumA tumors [12,15,16,28,30], whereas others found no such association [19,29,[31][32][33][34]. Only few studies have more than five years of observation time [9,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observed that HER2 þ and/or Basal subtype tumors have a significantly higher risk of local failure than LumA tumors [12,15,16,28,30], whereas others found no such association [19,29,[31][32][33][34]. Only few studies have more than five years of observation time [9,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have indicated a strong prognostic relation between patients with TNBC and increased LRR, and this also applied to early stage breast cancer. [10][11][12][13]18 In patients with ETNBC, Abdulkarim et al 14 recently reported that the LRR risk in the modified radical mastectomy without PMRT group was 2.5 times higher than in the breast-conserving therapy group among those with T1-T2N0 disease (4% vs 10%; P 5 .027). This has sparked an intense debate about re-evaluating the role of PMRT for ETNBC, a subgroup for which it was previously assumed that PMRT was not clearly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…More studies since have demonstrated that patients who have TNBC are at a higher risk of LRR, 10,11 including those who have very early disease. 12,13 Moreover, in a recent article by Abdulkarim et al 14 reporting exclusively on TNBC, the highest LRR rates were observed in patients who underwent modified radical mastectomy without PMRT compared with those who underwent modified radical mastectomy and received PMRT or breast-conserving therapy. This highlights the need to re-evaluate prognostic factors in early stage TNBC (ETNBC) and the utility of PMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing outcomes between the different subtypes have shown that her2 overexpression, which is found in 15%-20% of human breast cancers 3 , is associated with increased risk of locoregional recurrence [4][5][6][7][8][9] and increased breast cancer mortality [9][10] . Overexpression of her2 is thus generally considered to be a negative prognostic feature with an increased adjusted risk of breast cancer mortality that is approximately doubled 11 .…”
Section: Introductionmentioning
confidence: 99%